Detection of the cytochrome b mutation G143A in Irish Rhynchosporium commune populations using targeted 454 sequencing. Issue 6 (10th November 2016) - Phelan, Sinead; Barthe, Marie‐Sophie; Tobie, Camille; Kildea, Steven
Abstract: BACKGROUND: Rhynchosporium commune is a major fungal pathogen of barley crops, and the application of fungicides, such as quinone outside inhibitors (QoIs), plays an important role in crop disease control. The genetic mechanisms linked to QoI resistance have been identified in the cytochrome b gene, with QoI resistance conferred by the G143A substitution. The objective of this study was to develop a high‐throughput molecular assay to detect and identify mutations associated with QoI resistance within the Irish R. commune population. RESULTS: Leaf lesions of R. commune sampled from 74 sites during 2009–2014 and isolates from 2006 and 2007 were screened for non‐synonymous mutations of the cytochrome b gene using 454 targeted sequencing. The presence of the G143A substitution was confirmed in R. commune samples at one site in 2013 and at four sites in 2014; however, the frequency of the substitution in these samples was low (2–18%). The 454 sequencing results were confirmed by PCR‐RFLP and Sanger sequencing. CONCLUSION: The molecular assay that has been applied to this monitoring programme has shown that the application of 454 next‐generation sequencing offers the potential for high throughput and accurate characterisation of non‐synonymous mutations associated with fungicide resistance in a crop pathogen. © 2016 Society of Chemical Industry